The Role Of Legal Language In Formulatıng Wrıtten Legal Rules In Indonesıa - Junaedi Junaedi; Jaya Mulya (Cita Konsultindo Research Center, 2023)
Legal language is a regulatory language that is intended to realize justice and care for the community and is expected to protect private and public interests. Because the legal language is modern Indonesian, the use of Indonesian must be clear, fixed, mono-semantic, and in accordance with the aesthetic requirements of the Indonesian language. Thus, to understand the rule of law and legal language, in principle, it is a unity in a legal discipline. If you want to learn and understand the rule of law, you must use good legal language. The rule of law consists of a systematic legal language, From this view it is very clear, that the role of legal language is very important to formulate legal rules in society. The problem is how to apply the rules of legal language and the form of the legal language used in formulating written legal rules in Indonesia. This study aims to determine the role of legal language in formulating written legal rules in Indonesia. While the (type of research is normative legal research, namely legal research conducted by researching library materials, or secondary data, or library research. And the results of this study, First; the rules of legal language to formulate written legal rules are (1) Luges and exact; (2) Objective; (3) Careful definition; (4) Not emotional; (5) the exposure is conventional; (0) Not dogmatic (7) thrifty; (8) The form of the meaning is stable. Second; form of legal language to formulate legal rules; () The form of the word must be correct; (2) The meaning of the word must be precise; (3) Sentences must be clear; (4) Distinctive terms; (5) Not greeting people; (6) Typical wearing style; (7) The writing follows the EYD; (8) Legal norms are conveyed through sentences.